Repertório ocupacional infantil: opressões, resistências e as marcas da desigualdade social - Elias, Carina Sousa (2025)
Occupations structure daily life, give meaning to life, and shape the trajectory of individuals and groups, playing a fundamental role in the dynamics of social, economic, and political processes. Considering the impact of social inequality on childhood and occupational opportunities, this study investigated how socioeconomic condition influences the construction of children's occupational repertoires, mapping occupational opportunities in contexts of greater and lesser socioeconomic privilege based on children's reports, and understanding caregivers' perceptions of how the context shapes children's experiences. The exploratory research with a quantitative and qualitative approach involved 35 families from São Caetano do Sul/SP and Santo André/SP. Semi-structured interviews and Checklist Intersetorial de Detecção de Risco ao Desenvolvimento Infantil (CIDRDI) were applied to caregivers, and the Paediatric Activity Card Sort (PACS) to children aged 5 to 14. Data were analyzed using descriptive statistics from CIDRDI, inferential statistics from PACS, and Thematic Analysis of the interviews. The results of the PACS did not indicate significant differences in the occupational profile between the groups, and most children presented "low risk" for development in CIDRDI. However, the thematic analysis of the interviews revealed five crucial themes that permeate the plurality of childhoods of the study and cross children's occupations: (01) public policies for childhood; (02) areas of urban occupation as a possibility of access to housing; (03) the Bolsa Família Program: between subsistence and subjugation in the capitalist plot; (04) the nuances of the presence of organized crime as part of childhood spaces; (05) between barriers and possibilities: intersectionality in children's occupational dynamics; and culminating with Buen Vivir as a new meaning for childhoods and human occupations. Finally, it is worth highlighting that the theoretical production and interpretations woven in this research based on the life narratives of the participants had the purpose of understanding to what extent occupational opportunities are present in such plural childhoods. The study reaffirms that aspects such as food deprivation, precarious housing, difficulties in accessing public policies, violence by criminal organizations, State omission, and other factors linked to intersectionality that result in oppression and exclusion, more directly affect people in situations of social vulnerability, denying autonomy in their choices and occupational opportunities and perpetuating occupational apartheid. And that Buen Vivir emerges as a viable alternative for children to have significant opportunities to build their occupational repertoire.